2007
DOI: 10.1007/s11434-007-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on wavy distribution of rainfall associated with typhoon Matsa (2005)

Abstract: An analysis is made to investigate the structure features of the extensive heavy rainfall left by typhoon Matsa, after its landfall in mainland China in August 2005, based on a range of observational results, including surface intensive observation data, TBB data from China's FY-2 satellite, and NCEP 1°×1° reanalysis data. The study tries to explore the interaction between atmospheric waves, 3-D atmospheric structures, and typhoon rainbands. Observational facts, diagnostic analysis, and atmospheric wave theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Previous studies have mostly focused on precipitation directly caused by a TC either over the open ocean (e.g., Wang and Holland 1996a,b;Rogers et al 2003;Atallah et al 2007) or approaching-making landfall (e.g., Li et al 2007;Kimball 2008;Chen et al 2006). These studies have shown that over the open ocean, the rainfall distribution in a TC is largely controlled by the vertical shear in the large-scale environmental flow and the translation speed of the storm itself; whoever, after landfall, both the rainfall intensity and the radial extent of the outer rainfall are also affected by the soil moisture of the underlying land surface.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mostly focused on precipitation directly caused by a TC either over the open ocean (e.g., Wang and Holland 1996a,b;Rogers et al 2003;Atallah et al 2007) or approaching-making landfall (e.g., Li et al 2007;Kimball 2008;Chen et al 2006). These studies have shown that over the open ocean, the rainfall distribution in a TC is largely controlled by the vertical shear in the large-scale environmental flow and the translation speed of the storm itself; whoever, after landfall, both the rainfall intensity and the radial extent of the outer rainfall are also affected by the soil moisture of the underlying land surface.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, cluster analysis [30] was employed to analyze the relationship between the seasonal/interdecadal variations and the abnormal variations in the polar vortex, in an attempt to develop an approach for evaluating and predicting seasonal and annual SDS intensity. Figure 1 shows 100 hPa anomalies where SDS weather occurred either in a raised or reduced number during the period 1980-2006.…”
Section: Analysis Of Synthesized Datamentioning
confidence: 99%
“…With excellent wear resistance, corrosion resistant, thermostability, the TiCN ceramic composite material has been used to improve surface properties of the cutting tool and machine parts widely. The main preparation technology of TiCN coating such as plasma chemical vapor deposition (PCVD) [1], plasma spraying (PS) [2] and reactive electric spark deposition (RESD) [3][4][5] and so on, have some drawbacks in some degree, such as process complex, high cost and thickness thin. Reaction nitrogen arc welding cladding can be used to process TiCN coating with tungsten electrode as a cathode, metal substrate precoated graphite powder and titanium powder as an anode, and high purity nitrogen as protection and response gas [6].…”
Section: Introductionmentioning
confidence: 99%